Association of Technetium(99m) MAG-3 renal scintigraphy with change in creatinine clearance following chemoradiation to the abdomen in patients with gastrointestinal malignancies - May, Kilian Salerno (Pioneer Bioscience Publishing Company, 2010)
BACKGROUND: Information on differential renal function following abdominal chemoradiation is limited. This study evaluated the association between renal function as measured by biochemical endpoints and scintigraphy and dose volume parameters in patients with gastrointestinal malignancies. MATERIALS AND METHODS: Patients who received abdominal chemoradiation between 2002 and 2009 were identified for this study. Technetium(99m) MAG-3 scintigraphy and laboratory data were obtained prior to and after chemoradiation in 6 month intervals. Factors assessed included age, gender, hypertension, diabetes, and dose volume parameters. Renal function was assessed by biochemical endpoints and renal scintigraphy. RESULTS: Significant reductions in relative renal function of the primarily irradiated kidney and creatinine clearance were seen. Split renal function decreased from 49.75% pre-radiation to 47.74% and 41.28% at 6-12 months and >12 months post-radiation (P=0.0184). Creatinine clearance declined from 90.67ml/min pre-radiation to 82.23ml/min and 74.54ml/min at 6-12 months and >12 months post-radiation (P<0.0001). Univariate analysis of patients who had at least one post-radiation renogram showed the percent volumes of the primarily irradiated kidney receiving ≥ 25 Gy (V(25)) and 40 Gy (V(40)) were significantly associated with ≥5% decrease in relative renal function (P=0.0387 and P=0.0438 respectively). CONCLUSION: Decline in split renal function using Technetium(99m) MAG-3 scintigraphy correlates with decrease in creatinine clearance and radiation dose-volume parameters following abdominal chemoradiation. Change in split perfusion can be detected as early as 6 months post-radiation. Scintigraphy may provide early determination and quantification of subclinical renal injury prior to clinical evidence of nephropathy.